Perception and Knowledge Level of Yam Farmers on COVID-19 Pandemic in Taraba State, Nigeria (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The main objective of the study was to determine the perception and knowledge of yam farmers on COVID-19 pandemic in Taraba State. A total of 120 respondents were purposively selected from 8 village communities of 4 local government areas of the state. The local government areas were: Wukari, Ibbi, Yorro and Zing. Data were collected on perception of farmers on COVID-19 pandemic, knowledge of yam farmers on COVID-19 disease and farmers source of information on COVID-19 pandemic.  Data collected were presented using frequency and percentages, mean score and standard deviation. The result of the analysis revealed that the respondents perceived that COVID-19 pandemic poses danger to livelihood (=3.79), COVID-19 pandemic exists (=3.54), COVID-19 pandemic is contagious (=3.48) and COVID-19 pandemic brought health complications to farmers (=3.47). Respondents had good knowledge of COVID-19 pandemic as the majority (76.7%) know that maintaining social distance can prevent COVID-19 infection, about 76% were aware that COVID-19 is a contagious disease and 74.2% were knowledgeable that hand washing with soap on a regular basis can help to prevent COVID-19 infection. Respondents had multiple sources of information on COVID-19 pandemic as all (100%) of the farmers cited radio as a source of their information on COVID-19 pandemic, 90.8% rely on family members and 90% rely on friends as a source of their information on COVID-19 pandemic. It was recommended that government should establishing institutional frameworks, policies and procedures for pandemic preparedness and response.
Keywords: Farmers; COVID-19; Knowledge Pandemic; Perception